As duas faces das técnicas de gestão: aprendizagem e inovação evidências de empresa do setor siderúrgico no Brasil - Louro, Sidney Sousa (2008)
AlI over the last 20 years there has been a profusion of studies that examine, at the level of enterprises, the contribution of the mechanisms of learning and adoption of management techniques to the process of technological accumulation. However, there are still few studies that examine, on a joint and in a dynamic perspective, the relationship between the adoption of management techniques, mechanisms and learning trajectories of accumulation of technological capabilities. More than that, there is a lack of studies to examine the dual role of management techniques, sometimes as part of the stock of technological capabilities, or as a process of technologicalleaming in itself. This task aims to offer a contribution to filI this gap in this field of study. The focus of this task derives from empirical observations, made at the leveI of enterprises, and is inspired by the classic study Innovation and Learning: the two faces of R&D, Cohen and Levinthal (1989). So, this task is based on an individual case study, conducted in a steel company in the sector in Brazil, from 1984 to 2008, examining these issues in light of analytical models available in the intemationalliterature. In this effect, the view of technology as a set of resources to generate and manage technological change was adopted, being built and accumulated gradualIy from the engagement in learning processes and coordination of bases of knowledge accumulated in different dimensions, symbiotic relation. The metrics used identify types and levels of technological capacity to different functions and identify four types of processes of technologicalleaming and evaluate in terms of its key features. Based on qualitative and quantitative empirical evidences, obtained first-hand and based on fieldwork, this task found that: 1. The company accumulated leveIs of innovative technological capabilities in alI the functions examined, the Innovative Intermediate levei (Levei 5) functions in Project Engineering (incomplete) and Equipment and the Advanced Intermediate level (Level 6) for the functions of Production Processes and Organization and Products. 2. The leaming mechanisms underlying to the accumulation of those levels of technological capacity showed relevant results in terms of its key features, especialIy to the variety and intensity: of 24 mechanisms in 1984 to a total of 59 in 2008, with a variation of 145,8%, and with 56 ofthe 59 mechanisms (94.92%) are current1y used in a systematic manner. 3. The period between the years 1990 and 2004, which were implemented the management techniques studied (except the Plano de Sugestões), is characterized by having a higher rate of accumulation of technological capabilities and by initiating the use of almost alI the 35 new learning mechanisms built by the company afier it began its operations (1984). And that the management techniques studied: 1. Contributed to the process of technological leaming of AMBJF, mainly by the needs to: (i) incorporate new leaming mechanisms enabling it to colIect in advance, the knowledge base necessary to implement management techniques studied, (ii) coordinate a greater number of the appropriate mechanisms that would support the increased complexity of its Sistema de Gestão Integrada (SGI). 2. Expanded, in itself, the stock of the company's technological capabilities, specifically in its organization, from the accumulation of knowledge in procedures, work instructions, manuaIs, processes and tlows of management and production, among others. Thus, the results found by this task confirm that the adoption and implementation of management techniques studied contributed to and intluence the process of technological leaming and accumulation of technological trajectory of the company, while exercising, therefore, a dual role in the organization. This conclusion leads us to a better understanding of the theme and can contribute to the understanding of policy and management actions that might accelerate the accumulation of technological capabilities, understanding the relevance of management techniques less in terms ofits 'mere' adoption and more oftheir the implementation processo